Rancang Bangun Sistem Informasi Manajemen Presensi Pegawai STAB Negeri Raden Wijaya - Adi Nugroho Susanto Putro (Departement of Mathematics Education, 2022)
Presence Management Information System can monitor employee productivity through attendance. By looking at attendance data, leaders can assess whether employee productivity has increased or decreased. STAB Negeri Raden Wijaya does not yet have a Presence Management Information System that can automatically record employee attendance because they still use Google Forms. This study aims to design and build an Employee Presence Management Information System at Raden Wijaya Wonogiri State Buddhist College with the Waterfall method. The stages are data collection, system analysis, system design, system development, system testing, system implementation and maintenance. Based on the results of the Black Box Testing test, the Presence Management Information System for STAB Negeri Raden Wijaya which was developed in this study functionally all modules can function properly. And based on the results of the User Acceptance test, the following results were obtained: as many as 97.59% of employees said that the Raden Wijaya State Employee Presence Management Information System could be used properly on employee mobile phones, as much as 100% of employees said that the Raden Wijaya State Employee Presence Management Information System Wijaya makes it easier for employees to take attendance, as much as 98.80% of employees say that the Attendance Management Information System for State STAB Raden Wijaya makes it easy for employees to view attendance recaps, as much as 100% of attendance admin employees say that Raden Wijaya State Employee Presence Management Information System very helpful for admin attendance in monitoring attendance, as much as 100% of admin attendance employees said that the Attendance Management Information System for Civil STAB Raden Wijaya was very helpful for attendance admin in conducting attendance recap.